Photocatalytic reduction of CO2 by graphitic carbon nitride polymers derived from urea and barbituric acid - Qin, Jiani; Wang, Sibo; Ren, He; Hou, Yidong; Wang, Xinchen (Applied catalysis. B, Environmental, 2015)
[Display omitted] •Copolymerization and textural engineering were combined to modify the physicochemical properties of g-C3N4.•The g-C3N4 nanosheets were facilely synthesized by the condensation of urea and barbituric acid.•The modified g-C3N4 nanosheets photocatalyzed CO2 reduction with enhanced performance over g-C3N4. Conjugated carbon nitride nanosheets modified with barbituric acid (BA) were synthesized by a facile one-pot chemical condensation of urea. The obtained BA-modified carbon nitride samples were termed as CNU-BAX and were fully characterized by XRD, FTIR, XPS, NMR, EPR, FESEM, TEM, DRS, PL, BET and photocurrent measurements. The performance of the developed carbon nitride based semiconductors was investigated by applying them as polymeric photocatalysts for the reduction of CO2 under visible light illumination. Results revealed that the copolymerization of urea with BA co-monomer strongly alternated the physical and chemical properties of carbon nitride polymer by improving optical absorption and creating surface molecular heterojunction that promoted charge separation, and consequently the enhanced photocatalytic performance was achieved. Various reaction parameters were investigated and optimized for the reaction system, and we found that under the optimal reaction condition, the best sample (CNU-BA0.03) could effectively photocatalyze the CO2-to-CO conversion reaction with 15-fold-enhanced catalytic activity, compared to the non-modified sample derived from urea (named as CNU). Other typical comonomers were also selected to polymerize with urea to study the beneficial effect of copolymerization on the development of efficient carbon nitride based nanostructures for CO2 photoreduction.